Rooting of Shoot Cuttings of Dipterocarpus retusus Syn. D. macrocarpus - Thakur, Ajay; Sharma, Papori (Indian Forester, 2007)
A mist-less condition was created and root growth regulator Indole-3 butyric acid, Para Hydroxy benzoic acid (IBA and PHBA) was tried for rooting of stem cuttings in Dipterocarpus retusus. Cuttings were taken from three positions i.e., apical, middle and basal of nine months old seedlings. Adventitious rooting was obtained 18 % in case of shoots derived from middle portions of seedlings, however, shoots from apical and basal positions failed to root. Variation of rooting was non- significant in case of hormonal treatment. Sprouting occurs in shoots from all three positions and varied significantly due to its position (P<0.01) and growth regulator (P<0.05). Rooting occurred mostly at callus.